The Kyoto Protocol: A flawed concept - Richard N. Cooper (Fondazione Eni Enrico Mattei (FEEM), 2001)
The framework of the Kyoto Protocol, an agreement for the world's rich countries to reduce their greenhouse gas emissions, is deeply flawed. This paper explains why. The Protocol lacks essential country coverage, provides an inadequate basis for allocating emission rights, lacks provision for monitoring and enforcement, and implies politically unacceptable transfers among governments under a (necessary and desirable) arrangement for trading emission rights. In addition, it would by itself do little to limit climate change. An alternative approach to limiting greenhouse gas emissions is suggested, focussing on international agreement on common actions to reduce emissions.And contingency plans for adaptation to climate change and for sequestration greenhouse gases are urged.
Keywords: Q20; 330; Emissions trading; global climate change; greenhouse gases; Kyoto Protocol; Klimaschutz; Umweltabkommen; Kritik; Emissionshandel; Lizenz; Allokation; Welt